Mapping evidence on health promotion in HIV testing among men who have sex with men and transgender women using the social-ecological model and the vulnerability theoretical framework: a scoping review - Camila Amaral Moreno Freitas; Thais Aranha Rossi; Inês Dourado; Marcelo Eduardo Pfeiffer Castellanos; Nathalia Sernizon Guimarães; Laio Magno (BMC, 2023)
Abstract This study aimed to map the scientific evidence on health promotion in human immunodeficiency virus) HIV testing among men who have sex with men (MSM) and transgender women (TGW) based on the social-ecological model (i.e., individual, organizational and social levels) and the theoretical framework of vulnerability (i.e., individual, social, and programmatic levels). The reviewed studies indicated several barriers to accessing HIV testing (e.g., economic, structural, and bureaucratic) and demonstrated the potential for community approaches to promote greater access to HIV testing and minimize the stigma and discrimination associated with HIV testing, primarily through community leadership and social support networks. The socio-ecological model of health promotion and the vulnerability approach have the potential to contribute to improving HIV testing services by balancing the technical and political power of health services and providers with community participation while considering the social contexts. Therefore, there is a need for reflection on health promotion policies and programs aimed at expanding access to HIV testing among MSM and TGW through interventions that consider the social contexts and cultural perspectives. Moreover, inter-sectoral strategies aimed at improving living conditions and access to fundamental resources for maintaining health and well-being should be considered.